2021
DOI: 10.1002/anie.202114926
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Oxidative Addition and Reductive Elimination at Tin(I) via Hemi‐Lability

Abstract: We report on the synthesis of adistannyne supported by ap incer ligand bearing pendant amine donors that is capable of reversibly activating E-H bonds at one or both of the tin centres through dissociation of the hemi-labile N-Sn donor/acceptor interactions.This chemistry can be exploited to sequentially (and reversibly) assemble mixed-valence chains of tin atoms of the type ArSn{Sn(Ar)H} n SnAr (n = 1, 2). The experimentally observed (decreasing) propensity towards chain growth with increasing chain length ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Below 247 K, substantial signal broadening likely indicative of slower kinetics prevented acquisition of meaningful van't Hoff plots, especially considering the near thermoneutrality of this equilibrium (Δ G (298 K)=0.1 kJmol −1 ). These observations are complementary to recent work by the Aldridge group, who showed that reductive elimination and oxidative addition of tin hydrides to a formally Sn(I) centre was controlled by (de)coordination of a hemilabile ligand [22c] …”
Section: Resultssupporting
confidence: 71%
“…Below 247 K, substantial signal broadening likely indicative of slower kinetics prevented acquisition of meaningful van't Hoff plots, especially considering the near thermoneutrality of this equilibrium (Δ G (298 K)=0.1 kJmol −1 ). These observations are complementary to recent work by the Aldridge group, who showed that reductive elimination and oxidative addition of tin hydrides to a formally Sn(I) centre was controlled by (de)coordination of a hemilabile ligand [22c] …”
Section: Resultssupporting
confidence: 71%
“…Both 3 ‐Ge 2 and 3 ‐Sn 2 give rise a 13 C NMR resonance in the region characteristic of the [CO 3 ] 2− ligand (δ C =163.5 and 168.2 ppm, respectively, cf. 167.5 ppm for the related N i Pr 2 ‐ligated system (Ar iPr2 Sn) 2 (μ‐κ 1 (O)‐κ 2 (O′,O′′)‐CO 3 ), [14] and in the case of the tin compound, structural authentication was possible by X‐ray crystallography (Figure 2). The net conversion of two equivalents of CO 2 in this fashion to CO and a bridging carbonate ligand has previously been reported for only one distannyne system, [14, 17] while a small number of digermyne compounds have been reported to convert CO 2 into CO with accompanying formation of the corresponding bridging oxide [6f, 8] …”
Section: Methodsmentioning
confidence: 99%
“… Exploiting hemi‐lability in dimetallynes to control access to two‐coordinate Group 14 metal centres: applications in a) catenation; [13] b) reversible E−H bond activation; [14] and c) reversible CO 2 capture (this work).…”
Section: Methodsmentioning
confidence: 99%
“…[13,14] This approach can be exploited i) to generate extended chains of Ge I centres akin to oligo-acetylenes through the formation of Lappert-type double bonds between "decomplexed" metal centres (Scheme 2a); [13,15] and ii) to facilitate reversible bond activation via oxidative addition/reductive elimination at Sn I (Scheme 2b). [14] We also perceived that the versatile coordination capabilities afforded by hemi-labile donors would allow dimetallynes of this sort to participate in reaction chemistry generating metal centres with appreciably different electronic requirements (Scheme 2c). In particular, we hypothesized that this might allow for the isolation of molecular species (containing EÀ C and EÀ O bonds) resulting from direct insertion of CO 2 into the EÀ E bond.…”
mentioning
confidence: 99%